REPRESENTASI ANAK-ANAK DALAM TAYANGAN IKLAN KOMERSIAL DI MEDIA - Dian K Marhaeni (Program Studi Ilmu Komunikasi FBIK Unissula, 2010)
Children are orisinil person. The emerge children ini advertisement in television is prepared by ideologies and power interest. We saw advertising with constructivition and representative hipereality. Children are described more activity with identity of background that it is determined by capital owner. There are, children are represented capitalist of ideology in individualist, class, liberty, prosperity and alienacy. Also, Capital owner is working in economict interest to addition capital. Children are represented as healty child, clever, the highest their growing, much eating, life style, richt and the have sociaty. Children are created a consumers and star of child. At there contrary with realy condition. The goverment by profesion of organisation has to such a power rules that media and profesion can to implicated social responsibility.